2022
DOI: 10.1097/btf.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl Alcohol Hydrogel Hemiarthroplasty of the First Metatarsophalangeal Joint Augmented With 3D-printed Baseplate

Abstract: Hallux rigidus is the most common arthritic pathology of the foot and is a debilitating disease that causes pain, swelling, and reduced range of motion. Although arthrodesis is the gold standard treatment option, a soft hemiarthroplasty implant, the polyvinyl alcohol (PVA) hydrogel, has been designed to preserve motion in the first metatarsophalangeal joint and alleviate pain. Made from synthetic PVA and saline, the index noninferiority trial showed satisfactory clinical outcomes. However, this result was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They attributed this poor satisfaction rate to higher rates of psoriatic arthritis and concomitant sesamoidal arthritis of the female population in the sample. Additionally, they concluded that the higher prevalence of osteoporosis in postmenopausal women may impede the integrity of the press-fit technique of implant introduction into the metatarsal head [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed this poor satisfaction rate to higher rates of psoriatic arthritis and concomitant sesamoidal arthritis of the female population in the sample. Additionally, they concluded that the higher prevalence of osteoporosis in postmenopausal women may impede the integrity of the press-fit technique of implant introduction into the metatarsal head [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…After final fluoroscopic images were obtained, the MTPJ capsule and skin were closed in a layered fashion with vicryl suture for the deep layers and silk suture for the skin [ 20 ]. Postoperative oblique, anteroposterior, lateral, and weight-bearing films were obtained to confirm the proper placement of hardware (Figure 5 ).…”
Section: Methodsmentioning
confidence: 99%